(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
At the time of independence, India had a very poor infrastructure in terms of energy production and supply, total installed electricity generation capacity was 1363 MWe. Electricity is the most important component of the primary energy. The average growth rate over the entire period thus has been an impressive. The economics of various modes of power generation depends on local conditions, discount rates and availability of cheap fuels. India is importing coal hydrocarbons as well as enriched uranium. Issues like comparative economics, effect on environment, security of supplies, future technological developments in India will dictate contributions of various energy resources. The objective function of model is to minimize the cost associated with power generation from each resource. This Model is subjected to various constraints like potential, demand, efficiency, emission and H/C ratio, isolated load and minimum capacity existing. This model shows that 72% of total requirement can be met by Coal and Hydro power sources itself. From the renewable side, wind and bio gas can make up to 9% of total power requirement. Due to high running cost, solar importance maintains lowest in all scenarios. It’s compulsory to find advanced technology to reduce the cost of solar based power generation.